Persistence of regional entrepreneurship: Causes, effects, and directions for future research - Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena, 2017)
This paper reviews the empirical evidence of persistent levels of regional self-employment and new business formation and the effect this persistence has on development. It is argued that a regional culture of entrepreneurship plays an important role in explaining persistence of entrepreneurship. We discuss possible explanations for the emergence of a culture of entrepreneurship, and how it becomes self-perpetuating over time. Finally, we draw policy implications and identify some promising avenues for further research.
Keywords: L26; R11; O11; 330; entrepreneurship; economic development; entrepreneurship culture; institutions